Simulation of optimizing decisions and risk analysis in investment plans - Katona, Szilvia; Ertsey, Imre (Acta Agraria Debreceniensis, 2007)
Investments always contain risks, as data referring to the future are planned and uncertain. Therefore, besides feasibility analyses we need to perform risk analyses, as well. Through statistic simulation methods, our aim is to examine how uncertain and prospective data as risk factors affect investment-profitability indices. On the other hand, our aim is to find out the optimal innovation – financing decisions by using decision optimizingmethods.